Lean in, don't step back: The views and experiences of patients and carers with severe mental illness and incurable physical conditions on palliative and end of life care. (3rd September 2021) - Jerwood, J.; Ward, G.; Phimister, D.; Holliday, N.; Coad, J.
Abstract : Background and Aim: People with severe mental illness (SMI) have a life expectancy of up to twenty years less than the general population and many live with incurable physical health conditions. Yet, they continue to experience barriers when trying to access palliative and end of life care (PEOLC). Little research has been carried out which includes the views and experiences of people with SMI, and this study presents first findings which include people with both SMI and an incurable condition and their carers. It aimed to seek their views, and those of their carers, on their experiences and expectations of accessing PEOLC and to understand how PEOLC for people with SMI could be improved. Methods: Semi-structured interviews were carried out with 8 participants (5 patient participants and 3 carer participants). Thematic analysis of the interview transcripts was undertaken. Findings: Four over-arching themes were developed. (1) Stigma and Prejudice – See Me, Not My Diagnosis (2) Hesitancy and Avoidance – Treading on Eggshells (3) Collaborators in Care – The Ignored Experts and (4) Connections – Leaning in, Not Stepping Back. Significance of Findings: This study presents the first accounts from the UK concerning experiences of PEOLC, barriers to access and how care can be improved, from the perspectives of patients with both a SMI and an incurable physical condition and their carers. The findings illuminate an under-researched area of clinical practice and contribute rich understandings to future service developments and innovations.